OUT-OF-CLASS ACTIVITIES AS THE FACTOR OF SOCIAL SKILLS TRAINING OF TEENAGERS WITH VISION DISABILITY - Raudeliūnaitė, Rita (Acta Paedagogica Vilnensia, 2007)
The article raises the problem of developing social skills of teenagers with vision disability as an essential condition for social integration. Major attention is given to out-of-class activities as an important educational factor determining the dissemination of social skills. To this end the following essential criteria of activity efficiency assessment were distinguished: expedience of activity, significance of activity, level and degree of activity and humanness of relationship during the activity.The article analyzes the connection of activity expedience, personal and social significance and humanness of relationship with social skills. Statistical analysis has revealed significant connection between the expedience of teenager activities, significance of activity, level and degree of activity, humanness of relationship during the activity and social skills. This proves that specific goals matching the individual characteristics of teenagers, personal and social meaningfulness for the teenager and level and degree of teenager activity along with the humanness of relationship during the activity is an important prerequisite for the development of social skills. The research was aimed at analyzing whether activities arranged in special schools for students with vision disability are expedient, personally and socially meaningful and intensive and the relationship of teachers and students is humane. The research results revealed that teenagers often find the goals raised during out-of-class activities unclear, too complicated, and not complying with their interests, dispositions and needs and especially being beyond the level of their social skills. Surely, not clear and unrealistic goals hinder the purposeful arrangement of activities and achievement of the expected result; they also undermine the student’s self assessment. The activity not in tune with the teenager’s individual character lessens his interest in the activity thus weakening the educational effect of the activity.The data have also revealed that out-of-class activities have low personal and social significance for students. From the educational point of view personally not meaningful activity has no positive educational effect. Therefore during educational out-of-class activities students more often act as passive observers than active participants of the process. Besides, the efficient development of social skills is impossible without the activeness and independence of the student himself.The research also discovered that during out-ofclass activities students miss humanism in  teacherstudent relationship, namely sympathy and especially confidence in students, whereas human behaviour of teachers is an important benchmark of human behaviour of students. Human relationship of teachers with students helps to establish closer interrelationship, increase student self-confidence, encourage the expression of their humaneness and teach the culture of interrelationship.
Keywords: social integration; social skills; out-of-class activities; expedience of activities; meaningfulness; activity; humaneness